Analisis Lima Kekuatan Porter dan Swot untuk Perancangan Strategi Pemasaran Jasa Fotografi - Risa Aisyah (Institut Teknologi Garut, 2023)
This study aims to identify recommendations for service marketing strategies that can increase consumer interest in photography services in Garut Regency. The research method used is descriptive qualitative. Respondents in this study were selected using a purposive sampling technique, by selecting up to 5 respondents who have a good understanding of The Hoobs Studio and have authority in developing marketing strategies. The analysis technique used in this study includes Porter's five forces and SWOT analysis. The results showed that: 1) in the IFAS table, the weaknesses are more dominant than the strengths; 2) in the EFAS table, the opportunity factors are more significant than the threat factors, because the marketing strategy measures implemented have not reached their maximum potential, especially in terms of promotions through social media; and 3) there is no strategic policy that supports the development of the tourism industry, especially in the field of photography.